Perceptions of occupational social workers in Gauteng regarding their potential engagement in corporate social responsibility. - Dugmore, Carolyn Elizabeth (My University, 2014)
Occupational social work and corporate social responsibility share commonalities which could provide significant avenues for occupational social worker practice, especially at a macro level of intervention, the area most lacking in their service delivery. The engagement of occupational social workers in corporate social responsibility in South Africa seems to have been misunderstood, with consequent limited involvement of the profession in this field. The main aim of this qualitative exploratory study was to explore the perceptions of occupational social workers in Gauteng regarding their definition and envisaged engagement in corporate social responsibility interventions in order to motivate for the incorporation of corporate social responsibility into their practice. To achieve the aim of the study, semi-structured interviews were held with seven occupational social workers and three social workers with five years practical experience in occupational social work. Sampling was not necessary given the small size of the research population. Data analysis took the form of thematic content analysis. The main findings were that the participants’ primarily defined corporate social responsibility as the contribution made by companies to the community outside the workplace however, they subsequently identified internal stakeholders, such as employees, as legitimate recipients of corporate social responsibility services. The data analysis revealed a clear perception that occupational social workers were well-suited to play roles in corporate social responsibility, utilising a full range of their micro, meso and macro skills. The identification of avenues for macro practice with internal and external company stakeholders was particularly significant, given that this is the area of intervention which has been most lacking in occupational social work service delivery. It was also established that the objectives of developmental social welfare could be incorporated into occupational social work roles in corporate social responsibility. The conclusion was reached that occupational social workers could play valuable roles in the social responsibility endeavours of companies to contribute towards change efforts to address the social problems and transformation challenges which plague South African society. The support of company leadership, who are open to the ideas of occupational social workers and champion an increased mandate for them, would be facilitative to the development of an occupational social work domain in the field of corporate social responsibility.
Keywords: Corporate social responsibility; Occupational social work; Macro practice developmental social welfare